2018
DOI: 10.1080/10872981.2018.1505401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an education-centered medical home on quality at a student-volunteer free clinic

Abstract: Background: The continuity provided by longitudinal clerkships has documented benefits to medical student education. Yet, little quantitative data exist on the association between longitudinal clerkships and patient outcomes.Objective: This study compares screening metrics of a longitudinal clerkship called the education-centered medical home (ECMH) with the standard clinical model at a student-volunteer free clinic (SVFC). In the ECMH model, the same attending physician staffs one half-day of clinic with same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…36 O'Neill et al showed the feasibility of tracking quality metrics as part of a longitudinal clerkship with promising trends towards improved preventative care. 37 Patient outcomes data from one longitudinal clerkship demonstrated improved influenza vaccination rates and increased rates of screening for HIV, cervical cancer, and hepatitis C. 16,38 If structured and supervised properly, students may be able to serve as health coaches and quality managers for complex patients. 39 Further studies are clearly needed to replicate these early findings-but these future studies can only be done if longitudinal programs are sustained and expanded to additional institutions.…”
Section: Level 4: Change In Practice and Benefits To Patientsmentioning
confidence: 99%
“…36 O'Neill et al showed the feasibility of tracking quality metrics as part of a longitudinal clerkship with promising trends towards improved preventative care. 37 Patient outcomes data from one longitudinal clerkship demonstrated improved influenza vaccination rates and increased rates of screening for HIV, cervical cancer, and hepatitis C. 16,38 If structured and supervised properly, students may be able to serve as health coaches and quality managers for complex patients. 39 Further studies are clearly needed to replicate these early findings-but these future studies can only be done if longitudinal programs are sustained and expanded to additional institutions.…”
Section: Level 4: Change In Practice and Benefits To Patientsmentioning
confidence: 99%
“… 21 , 30 , 54 Other concepts that were used interchangeably with student-run included student-created ; student-developed , student-directed , student-driven , student-initiated , student-managed , student-operated , student-organized , student nurse-delivered , student pharmacist-led , student pharmacist-run , and student-volunteer . 6 , 7 , 29 , 55 - 63 In some cases, more than one term was used interchangeably within the same article, such as student-run and student-led . 6 , 62 - 67 …”
Section: Resultsmentioning
confidence: 99%
“…21,30,54 Other concepts that were used interchangeably with student-run included student-created; student-developed, student-directed, student-driven, student-initiated, student-managed, student-operated, student-organized, student nurse-delivered, student pharmacist-led, student pharmacistrun, and student-volunteer. 6,7,29,[55][56][57][58][59][60][61][62][63] In some cases, more than one term was used interchangeably within the same article, such as student-run and student-led. 6,[62][63][64][65][66][67] Several articles provided substantial and explicit descriptions of the student-run health initiative 6,29,35,61,63,68 and 16 authors provided definitions for the concept they used (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…16,29,30,32,36 If comparing with national screening rates for the uninsured only, all studies on breast cancer screening and five in ten studies on cervical cancer screening met or surpassed the national average. 28,31,32,36,37 This suggests that, while there is substantial variation, people receiving care at SRFCs can achieve similar rates of breast and cervical cancer screening when compared with insured and uninsured populations receiving care at established settings, but further work is needed to close gaps in preventative care.…”
Section: Discussionmentioning
confidence: 99%